Individual and organizational resilience—Insights from healthcare providers in Germany during the COVID-19 pandemic - Gröschke, Daniela; Hofmann, Elisa; Müller, Nadine D.; Wolf, Judith (Frontiers in Psychology, 2022)
We explored the effects of resilience in the healthcare setting during the COVID-19 pandemic in Germany. Our study sheds light on the cross-level effects of resilience in hospitals and thus responds to calls to research this empirically. In a cross-sectional study design, perceptions of resilience of employees in hospitals and of transformations at the individual, team, and organizational level were analyzed. An online survey was conducted in summer 2020 in Germany in which 1,710 healthcare workers completed a self-report questionnaire. Results indicate that resilience is both a highly interrelated construct on the individual, team, and organizational levels and also positively linked to perceptions of transformation as an indicator for demonstration of resilience. We also found a partial mediation effect of organizational resilience and team efficacy, respectively, on the relationship between individual resilience and perceived transformation on the individual and organizational level as well as a full mediation on the team level. The study highlights the interdependence of individual and organizational resilience (which is mediated by team efficacy) and its impact on perceived transformation in German hospitals during the COVID-19 pandemic. Whereas team efficacy is crucial for performance in regular work operations, during a pandemic the organizational level becomes more relevant. Theoretical and practical implications are discussed.